New insights into glyphosate adsorption on modified carbon nanotubes via green synthesis: statistical physical modeling and steric and energetic interpretations (2021)
The present work used a statistical physics approach to present new insights into the adsorption of the pesticide glyphosate on modified carbon nanotubes via green synthesis (MWCNT/MPNs-Fe). The experimental equilibrium curves obtained for this system under pH 4 at temperatures 298, 308, 318, and 328 K were simulated from monolayer, double layer, and multilayer models, with 1 and 2 energies, considering real and ideal fluid approaches. Taking into account the statistical indicators and the physical meaning of the parameters, exploring simplifying hypotheses, the Hill model with 1 energy and ideal fluid approach (M1) presented the best prediction of the experimental data, indicating that glyphosate adsorption occurs by the formation of a monolayer and that pesticide interaction with MWCNT/MPNs-Fe are characterized by only one energy. Based on this approach, to assess the steric aspects of the system, the number of molecules adsorbed per site (n), the density of receptor sites (Nm), adsorption capacity at saturation (Qsat), and concentration at half-saturation (W) were interpreted. As for the energetic aspects, the adsorption energy (ΔE) was inferred. The combination of parameters to its evolution with temperature and the magnitude of ΔE indicated an exothermic process involving a physical interaction mechanism. Finally, the new insights showed that the MWCNT/MPNs-Fe adsorbent favored pesticide adsorption by interacting glyphosate molecules with the metallic iron nanoparticles present on the adsorbent surface. © 2021 Elsevier B.V.